Genome sequence and description of Mannheimia massilioguelmaensis sp. nov. (November 2015) - Hadjadj, L.; Bentorki, A.A.; Michelle, C.; Amoura, K.; Djahoudi, A.; Rolain, J.-M.
Abstract: Strain MG13 T sp. nov. is the type strain of Mannheimia massilioguelmaensis, a new species within the genus Mannheimia . This strain was isolated from the exudate of a skin lesion of an Algerian man. Mannheimia massilioguelmaensis is a Gram-negative, facultative anaerobic rod, member of the family Pasteurellaceae . Here we describe this organism, together with the complete genome sequence and annotation. The 2 186 813 bp long genome contains 2048 protein-coding and 55 RNA genes, including eight rRNA genes.